Board of directors and the internationalization process: The case of Romania - Ovidiu-Niculae Bordean; Anca Borza (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
This paper attempts to describe the relationship between some board composition (board size, board age, CEO-duality and female representation) and the internationalization strategy in Romanian firms. The data for our study was collected through secondary sources and was aimed at a sample of companies listed at Bucharest Stock Exchange (BSE). We had included in our survey both companies that were pursuing an international strategy and companies that were showing no interest for the internationalization process. The degree of international involvement of the listed companies was assessed through two dimensions: propensity for export and export intensity. The results of the analysis show that the internationalization path followed by the Romanian listed companies is not influenced in any way by board of directors. However, the number of years that the companies are listed on the stock exchange is a good predictor of internationalization.
Keywords: 650; cBoard of directors; internationalization strategy; export propensity; export intensity; corporate governance